2021
DOI: 10.3389/fendo.2021.744647
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Herbal Medicines for the Prevention of Glucocorticoid-Induced Osteoporosis

Abstract: Glucocorticoids are drugs that are widely used to suppress inflammation and the activation of the immune system. However, the prolonged use or at high doses of glucocorticoid can result in adverse side effects including osteoporosis, bone loss, and an increased risk of fracture. A number of compounds derived from natural plant sources have been reported to exert anti-inflammatory activity by interacting with the glucocorticoid receptor (GR), likely owing to their chemical similarity to glucocorticoids, or by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…According to our clinical experience, we believe that patients should be given methylprednisolone to inhibit the damage to follicles caused by effector T lymphocytes and prevent the progression of the disease 19 . Glycyrrhizin, the main component of compound glycyrrhizin tablets, has effects similar to those of steroid hormones but without hormone‐related adverse reactions 20 . These two drugs can regulate immunity, reduce inflammation‐induced damage to the hair follicle growth cycle, restore the normal growth cycle of hair follicles, and promote hair growth.…”
Section: Discussionmentioning
confidence: 99%
“…According to our clinical experience, we believe that patients should be given methylprednisolone to inhibit the damage to follicles caused by effector T lymphocytes and prevent the progression of the disease 19 . Glycyrrhizin, the main component of compound glycyrrhizin tablets, has effects similar to those of steroid hormones but without hormone‐related adverse reactions 20 . These two drugs can regulate immunity, reduce inflammation‐induced damage to the hair follicle growth cycle, restore the normal growth cycle of hair follicles, and promote hair growth.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial properties of Chinese herbal medicine in clinical and experimental osteoporosis therapy are currently supported by published research and clinical studies ( Zhang et al, 2016 ). Multiple research reports have demonstrated that Chinese herbal medication could help individuals with GIOP elevate their bone density and relieve their clinical symptoms ( Zhang et al, 2021 ). Epimedii herba is a natural chemical that is progressively being explored in the treatment and prevention of osteoporosis due to its pharmacological properties of reducing bone resorption and accelerating bone formation ( Ming et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to directly stimulating the osteogenesis of MSCs, flavonoids could also indirectly affect the osteogenic differentiation of MSCs by their well-known antioxidant and anti-inflammatory properties ( Schilling et al, 2014 ; Zhang ND. et al, 2016 ; Zhang L. et al, 2021 ). Besides, flavonoids were also loaded on bioscaffolds for the promotion of MSCs self-renewal and differentiation in bone regeneration.…”
Section: Effects Of Flavonoids On Osteogenic Differentiation In Of Me...mentioning
confidence: 97%